HIV-Infected Patients With Anal Cancer Precursors: Clinicopathological Characteristics and Human Papillomavirus Subtype Distribution - Liu, Yuxin; Sigel, Keith M.; Westra, William; Gitman, Melissa R.; Zheng, Wenxin; Gaisa, Michael M. (Diseases of the colon & rectum, 2020)
BACKGROUND:People living with HIV have high rates of anal human papillomavirus infection and anal precancer/cancer. OBJECTIVE:This study aims to1) determine human papillomavirus subtype distribution among people living with HIV with anal high-grade squamous intraepithelial lesions; 2) compare the clinicopathological characteristics of patients with anal high-grade squamous intraepithelial lesions by human papillomavirus 16 status; and 3) investigate high-risk human papillomavirus negative anal high-grade squamous intraepithelial lesion cases. DESIGN:In this retrospective study, 700 people living with HIV who have biopsy-proven anal high-grade squamous intraepithelial lesions were reviewed for demographics, cytological diagnoses, and human papillomavirus testing results for human papillomavirus 16, 18, and 12 other high-risk types. For human papillomavirus-negative subjects, corresponding biopsies were genotyped by using real-time polymerase chain reaction. SETTINGS:This study was conducted in a large urban HIV clinic system and major referral center for anal cancer screening. PATIENTS:Median age was 46 years (range, 20–76). Ninety-one percent of the patients were men who have sex with men. MAIN OUTCOME MEASURES:The primary outcome measure was the association between demographic variables and human papillomavirus 16 status. RESULTS:Anal cytology was unsatisfactory (5%), benign (13%), atypical squamous cells of undetermined significance (35%), low-grade squamous intraepithelial lesion (36%), and high-grade squamous intraepithelial lesions (11%). Human papillomavirus cotesting results were negative (n = 38, 5%), human papillomavirus 16 (n = 303, 43%), human papillomavirus 18 (n = 78, 11%), or exclusively non-16/18 types (n = 281, 40%). Human papillomavirus 16 positivity was associated with ≥3 high-grade lesions and ≥ low-grade squamous intraepithelial lesion cytology (p < 0.001). Age, race/ethnicity, sex, smoking, CD4+ T-cell count, and HIV viral load did not differ by status of human papillomavirus 16 (p > 0.05). For human papillomavirus-negative cases, human papillomavirus genotyping of biopsies was positive for high-risk (n = 14, 36%) or possibly carcinogenic types (n = 12, 32%), or negative (n = 12, 32%). LIMITATIONS:This was a retrospective data analysis, and it pooled the results for 12 high-risk human papillomavirus types rather than individual types. CONCLUSIONS:Nearly all people living with HIV and anal high-grade squamous intraepithelial lesions test positive for high-risk human papillomavirus on anal swabs; negative results may be due to sampling error, L1-based polymerase chain reaction assay, or human papillomavirus types not captured by standard clinical assays. Patients who have human papillomavirus 16-positive anal high-grade squamous intraepithelial lesions are indistinguishable from others based on demographic and clinical characteristics, underscoring the potential role of human papillomavirus testing for anal cancer screening. See Video Abstract at http://links.lww.com/DCR/B208. PACIENTES PORTADORES DE VIH CON PRECURSORES DE CÁNCER DE ANOCARACTERÍSTICAS CLINICOPATOLÓGICAS Y DISTRIBUCIÓN DEL SUBTIPO VPHLos pacientes portadores de VIH tienen altas tasas de infección por VPH y alto riesgo de desarrolar lesiones precáncerosas / cáncerosas del ano.(1) Determinar la distribución del subtipo de VPH entre las personas portadoras de VIH con lesiones intraepiteliales escamosas anales de alto grado. (2) Comparar las características clinicopatológicas de pacientes con lesiones intraepiteliales escamosas anales de alto grado del subtipo VPH 16. (3) Investigar casos de lesiones intraepiteliales escamosas anales de alto grado negativas para el VPH de alto riesgo.Estudio retrospectivo sobre 700 personas portadoras de VIH con lesiones intraepiteliales escamosas anales de alto grado confirmadas por biopsia. Los datos fueron revisados para determinar información demográfica, diagnósticos citológicos y resultados de tipización en el VPH subtipos 16 y 18, y otros 12 tipos de alto riesgo. Para los individuos negativos al VPH, se analizó el genotipo en las biopsias correspondientes mediante test de PCR en tiempo real.Extenso sistema de clinicas urbanas tratando VIH y un importante centro de referencia para la detección del cáncer analla mediana de edad poblacional fue de 46 años (rango, 20–76). 91% eran hombres que tenían sexo con hombres.Asociación entre las variables demográficas y el estado del VPH subtipo16.la citología anal fue insatisfactoria (5%), benigna (13%), células escamosas atípicas de importancia indeterminada (35%), lesión intraepitelial escamosa de bajo grado (36%) y lesiones intraepiteliales escamosas de alto grado (11%). Los resultados de la prueba conjunta del VPH fueron negativos (n = 38, 5%), el virus del VPH subtipo 16 (n = 303, 43%), el VPH subtipo 18 (n = 78, 11%) o los subtipos exclusivamente no 16/18 (n = 281, 40%). La positividad del VPH subtipo 16 se encotraba asociado con ≥3 lesiones de alto grado y ≥ células escamosas atípicas en la prueba de citología de indeterminada importancia (p < 0.001). La edad, la raza / etnia, el sexo, el tabaquismo, el recuento de células T CD4 + y la carga viral del VIH no difirieron según el estado del VPH subtipo 16 (p > 0.05). Para los casos negativos al VPH, el genotipo del virus del papiloma humano de las biopsias fue positivo para los tipos de alto riesgo (n = 14, 36%) o posiblemente carcinogénicos (n = 12, 32%), o negativo (n = 12, 32%).Análisis de datos retrospectivos, con resultados agrupados para 12 tipos de VPH de alto riesgo en lugar de tipos individuales.Casi todas las personas portadoras de VIH con lesiones intraepiteliales escamosas anales de alto grado dan positivo para el VPH de alto riesgo al muestreo de hisopos anales; Los resultados negativos pueden deberse a un error en el muestreo y al análisis de PCR basado en L1 o subtipos de VPH no obtenidos en los ensayos clínicos estándar. Los pacientes con lesiones intraepiteliales escamosas anales de alto grado positivas para el VPH subtipo 16 no son identificables de los demás, en función de las características demográficas y clínicas, lo que minimiza el rol potencial de la prueba del VPH en la detección del cáncer anal. Consulte Video Resumen en http://links.lww.com/DCR/B208. (Traducción—Dr. Xavier Delgadillo)